[Glaumbær Church and Cemetery] - Streng, Evelyn Fiedler (1975)
Photograph of a Glaumbær church and cemetery. The white church with a red roof sits to the right, a small cross sat along its roof. A white fence sits in a rectangle beside a brown animal. A white cross sits in the grass to the right. White buildings with red roofs are visible in the background at the foot of a dark mountain.